An audit of CT chest surveillance following oral cancer treatment. Issue 6 (July 2016) - Nugent, G.; Hughes, T.; Hanlon, R.; Jones, H. Lewis; Rogers, S.N.
Abstract: Computed tomography (CT) of the chest is an integral part of the staging of patients with oral cancer. It identifies metastases, synchronous pulmonary primaries, and detects small nodules of indeterminate character that require a follow-up scan. We aimed to find out how many patients with small nodules had had subsequent scans, and the outcome of those who did. Between 2010 and 2013, 413 patients with oral squamous cell carcinoma (SCC) were treated with curative intent or were actively monitored at the Merseyside and Cheshire Regional Surgical Head and Neck Unit. A total of 324 (78%) had CT at diagnosis. The scans of 246 were clear, metastases were detected in 4, and 51 showed abnormalities. Forty-nine of the patients with abnormalities were recommended for further interval scans but only 20 (41%) actually had them. Further pathological findings were found in 11 (increase in the size of the nodule n = 2; metastatic disease n = 5; and primary pulmonary tumour n = 4). A substantial number of patients did not have the recommended follow-up scans and potentially serious disease was found in some who did. As a result of this audit we have changed the process regarding the booking of CT surveillance scans, and we now check periodically that they have been done. The audit will be repeated to include other sites in the head and neck.